A Review on Speed Control Techniques of Separately Excited DC Motor - Mahmoud Zadehbagheri; Rahim Ildarabadi; Majid Baghaei Nejad (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Nowadays, many moving devices receive their energy from a battery. DC motor is the most suitable option for these systems. In addition, the speed of these motors can be controlled easily and in the extensive range. Intelligent control methods are widely used in control of the industrial processes due to simplicity and high capabilities. In this paper, the fuzzy resistance speed controller has been designed and presented for DC motor. This controller stabilizes speed of motor in the desirable path despite changes of load torque or change of motor elements. One of the other features of this controller is the multivariate objective function which is able to supply dynamical behavior of the motor. Rapid response, permanent fault and low overshoot are about the other advantages of this method. DOI:  http://dx.doi.org/10.11591/telkomnika.v13i1.7004